2017
DOI: 10.1088/1361-6463/aa8b06
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of multiple metal vapours into an arc plasma in gas tungsten arc welding of stainless steel

Abstract: A computational model of the mixing of multiple metal vapours, formed by vaporization of the surface of an alloy workpiece, into the thermal arc plasma in gas tungsten arc welding (GTAW) is presented. The model incorporates the combined diffusion coefficient method extended to allow treatment of three gases, and is applied to treat the transport of both chromium and iron vapour in the helium arc plasma. In contrast to previous models of GTAW, which predict that metal vapours are swept away to the edge of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
2
14
1
Order By: Relevance
“…This result suggests the presence of chromium ions near the electrode deformation region. It has also been reported that chromium ions are transported to the electrode by cataphoresis inside helium TIG arc plasma [9, 10]. For example, in thin film formation, metal ions are deposited on a solid surface when metal ions accelerated by an electric field collide with the solid surface [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests the presence of chromium ions near the electrode deformation region. It has also been reported that chromium ions are transported to the electrode by cataphoresis inside helium TIG arc plasma [9, 10]. For example, in thin film formation, metal ions are deposited on a solid surface when metal ions accelerated by an electric field collide with the solid surface [14].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, results clarified that, especially, chromium ions reached the arc centre and the electrode tip as time passed [7,8]. The transport mechanism of metal vapour inside an arc plasma was clarified using a two-dimensional axisymmetric computational model with a combined diffusion coefficient method developed by Park et al [9,10]. The combined diffusion coefficient method incorporates diffusion caused by four driving forces: gradient of the composition, temperature, pressure, and the applied electric field [11].…”
Section: Introductionmentioning
confidence: 99%
“…copper and nickel, which evaporate at different rates. Including both of them self-consistently would be very difficult, although not impossible [43]. However we can use of a uniform distribution of copper vapour as an approximate approach to understanding the influence of metal vapour.…”
Section: Cfd Simulationmentioning
confidence: 99%
“…Temperature distribution and the pool geometry do change with time during welding. Heat transfer occurs during the welding process due to different temperature distributed in the workpiece by local heating [17,18]. The fundamental modes of heat transfer are conduction, convection and radiation.…”
Section: Theoretical Analysismentioning
confidence: 99%